Should Democracy Grow up? Children and Voting Rights - Steven Lecce (Intergenerational Justice Review)
This paper examines whether or not children’s continued electoral exclusion is morally defensible. Ultimately, there is a deep tension between the egalitarian presuppositions of democracy and our apparent unwillingness to grant children voting rights. Unless a plausible distinction can be found, then, between adults and children that also tracks the underlying reasons for endorsing democracy in the first place, the continued political disenfranchisement of our youngest citizens is shown for what it is: social injustice. e paper begins by exploring some of the conceptual difficulties that childhood creates in relation to democracy. It then assesses the implications of two very different approaches to democracy for children’s voting rights: proceduralism and a child’s supposed right to an open future.